Analisis Penerapan PSAK 109 pada Badan Amil Zakat Daerah (BAZDA) Provinsi Kalimantan Barat - B41108114, ARIF Masbukhin (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2012)
Zakat is one of the three pillars of Islam, the charity can help ease the burden of others, especially the poor. It is necessary for the proper management and trustful. The purpose of this study was to determine the reporting and management of the implementation of zakat, Badan Amil Zakat Daerah (BAZDA) West Kalimantan Province in accordance with PSAK 109 and determine the factors that make PSAK 109 can not be applied. This research is a qualitative descriptive method. The method of data collection in the form of primary data and secondary data through interviews and observations. The analytical tool used in this study is PSAK 109. Techniques of analysis in this study is to analyze the application of PSAK 109 on BAZDA West Kalimantan Province. There are four aspects on which the analyzes SFAS 109, namely: the recognition, measurement, presentation and disclosure. In the presentation aspect Bazda West Kalimantan only use the annual report in the form of data reception and distribution of zakat, infaq and alms. So it is very difficult to know the financial condition of the province of West Kalimantan Bazda thoroughly. From a few paragraphs in PSAK 109, Bazda West Kalimantan has not been fully able to implement PSAK 109. This is due to the lack of acceptance of zakat, alms infaq and non-cash form and the lack of separation between fund halal and non-halal funds. Keywords: OPZ Practiced Accounting, Zakah Accounting, Religious Accounting, Applied Fund Accounting